Leading the revolution - Hamel, Gary (Harvard Business School P. BostonUS, 2000)
Presents radical innovation in companies, as the competitive advantage for this millennium. Explains the underlying principles of radical innovation; and provides a blueprint for creating the industry revolutions that will engineer prosperity in the new economy. Details steps for making innovation an enduring capability.